Kompetensi Strategik dalam Organisasi: Systematic Literature Review tentang Dynamic Capabilities dan Firm Performance - Bhagaskara Adiwidya Bhadra (Jurnal Riset Akuntansi, 2026)
Research on strategic competence has grown significantly due to digital transformation, global competition, and increasing business complexity. However, studies integrating strategic competence, dynamic capabilities, and firm performance through a systematic literature review remain limited. This study aims to examine research trends, dominant themes, theoretical perspectives, and future research directions related to strategic competence in modern organizations. This study employed a Systematic Literature Review based on PRISMA 2020 guidelines using data from the Scopus database with keywords related to strategic competence, strategic capability, core competence, and dynamic capability. The initial search identified 15,943 documents, and after several screening stages, 73 relevant articles were selected as the final dataset. The findings indicate that research on strategic competence increased significantly during 2021–2026. Dominant themes include dynamic capabilities, strategic agility, resource-based view, innovation capability, and firm performance. The study also shows that strategic competence research is evolving toward adaptive, knowledge-based, and sustainability-oriented perspectives. This study provides a comprehensive understanding of strategic competence research developments and offers insights for organizations in strengthening adaptability, innovation capability, and competitive advantage in dynamic business environments.